Relationship between aerobic parameters and intermittent high-intensity effort performance - Kalva-Filho, Carlos Augusto [UNESP]; Loures, João Paulo [UNESP]; Franco, Vanessa Holtz; Kaminagakura, Edson Itaru; Zagatto, Alessandro Moura [UNESP]; Papoti, Marcelo (FapUNIFESP (SciELO), 2013)
The purpose of the study was to examine the relationships between intermittent high-intensity efforts (RAST) parameters and variables related to aerobic metabolism (anaerobic threshold; LAN, maximal oxygen uptake; VO 2MAX and velocity correspondent to VO2MAX;iVO 2MAX). Eight under-17 (U17) soccer players (16±1 years) participated in the study. The participants were submitted to a graded exercise test and six maximal sprints of 35m with 10 seconds of passive recovery between each effort (RAST). The RAST parameters were not significant correlated with VO2MAX and LAN. However absolute and relative mean power were significantly correlated with iVO2MAX (r=0.79 e r= 0.85, respectively). Furthermore, the fatigue index and the relative peak power were significantly correlated with the iVO2MAX (r=-0,57 e r=0,73, respectively). In conclusion, the only aerobic variable correlated with performance in consecutive efforts with brief recovery periods, such as RAST, is iVO2MAX.
Correlações entre parâmetros aeróbios e desempenho em esforços intermitentes de alta intensidade
Keywords: Aerobic fitness; Intermittent high-intensity effort; Soccer players